Heart perforation by pacemaker: a case report - Pankratjevaitė, Lina; Samiatina-Morkūnienė, Diana (Lietuvos chirurgija, 2015)
Background Cardiac perforation is a rare complication of pacemaker or implantable defibrillator implantation. Patients with cardiac perforation may present with various symptoms, and sometimes it creates real diagnostic difficulties. Case report We report the case of an 80-year-old patient with a sick sinus syndrome. He underwent the implantation of a dual chamber permanent pacemaker complicated by cardiac perforation, haemopericardium, and right haemothorax. The patient felt unwell a few hours after the procedure had been done. However, the cardiac perforation was confirmed by chest computed tomography just five days after the pacemaker implantation had been performed. Migrated lead was removed by an electrophysiologist with the backup of surgeons under thoracoscopy control. Next day the migrated lead was changed with a new one, and the patient left the hospital on the sixteenth day after pacemaker implantation. Conclusions Literature says that the big part of migrated pacemakers’ leads could be removed safely by simple traction under X-ray or echocardiography monitoring in the operating room, with a surgeon team backup. We have done it successfully with a thoracoscope control.